PELATIHAN BAHASA INGGRIS BAGI MAHASISWA AKPARTA SURAKARTA - Eka Susylowati; Ika Oktaria; Arini Hidayah; Yunita Widiyantari; Anik Astuti (LPPM Universitas Bina Bangsa, 2021)
This study aims to train English language skills for Akparta students to be proficient in English. The research methods used include presentations, lectures, observations and discussions. The results showed that the level of English mastery of the Surakarta Akparta students had progressed in speaking English. Community service activities carried out at Akparta Surakarta are helpful for students to improve their English language competence so that students can become professional tourism workers